Babad tanah jawi Mulai dari nabi sampai tahun 1647 Penysusun W.L Oithof; alih bahasa, HR Sumarsono; penyunting Floriberta Aning dan A. Yogaswara - OITHOF, W.L.; HR. Sumarsono; HR Sumarsono; A. Yogaswara (Narasi, 2014)
447 hlm.; 25 cm 25 cm